Postpartum Contraceptive Use In Parakou (A City In Northern Benin) In 2018: A Community Based Cross-Sectional Study - Hounkponou F; Glèlè Ahanhanzo Y; Biaou COA; Dos-Santos CR; Ahouingnan A; Obossou AA; Sidi Imorou R; Vodouhe M; Laourou H; Salifou K; Perrin RX (Dove Medical Press, 2019)
Fanny Hounkponou,1 Yolaine Glèlè Ahanhanzo,2 Chabi Olaniran Alphonse Biaou,2 Candide Russel Dos-Santos,1 Aurelle Ahouingnan,1 Awadé Achille Obossou,1 Rachidi Sidi Imorou,1 Mahublo Vodouhe,1 Hubert Laourou,3 Kabibou Salifou,1 René Xavier Perrin4 1Department of Mother and Child, Faculty of Medecine, University of Parakou, Parakou, Benin; 2Epidemiology and Biostatistics Department, Public Health Regional Institute, Ouidah, Benin; 3Public Health Department, Claude Bernard Lyon 1 University, Lyon, France; 4Department of Mother and Child, Faculty of Health Science, University of Abomey Calavi, Cotonou, BeninCorrespondence: Chabi Olaniran Alphonse BiaouEpidemiology and Biostatistics Department, Public Health Regional Institute, Ouidah, BeninTel +229 21 97730142Email alphonse.biaou@yahoo.frBackground: Over 30% of maternal deaths and 10% of infant deaths are avoidable if couples space out births at intervals of 2 years or greater. This study aimed to identify factors associated with contraceptive use in the postpartum period.Methods: This was a cross-sectional study among postpartum women living in Parakou. Participants were selected using a two-stage sampling method. Postpartum contraceptive use was defined as the use of at least one contraceptive method at the time of the survey. Independent variables included socio demographic and reproductive history. For the analysis we performed a multiple logistic regression and we calculated odds ratios with 95% confidence intervals.Results: The study included 453 postpartum women. Among the participants, 59 (13%) were using a contraceptive method. Injectable contraceptives were the most common method used (25.4%). Factors associated with contraceptive use in the postpartum period included history of contraceptive use (AOR=9.4; p<0.001), resumption of sexual intercourse (AOR=5.7; p<0.001), discussion with partner about contraceptive method (AOR=5.7; p=0.005), need of partner’s approval before adopting a contraceptive method (AOR=0.4; p=0.014) and counseling during pregnancy, in the delivery room, and during postnatal visits (AOR=2.7; p=0.019).Conclusion: The prevalence of contraceptive use during the postpartum period remains low. Interventions should be designed with a focus on the associated factors in order to increase postpartum contraceptive use in Parakou.Keywords: family planning, postpartum period, risk factors, Benin